Dampak Psikologis Terhadap Istri Yang Menjadi Korban Kekerasan Dalam Rumah Tangga Di P2tp2a Provinsi Kalimantan Timur Tahun 2014 - Rosdiana, Rosdiana (Jurnal Kesehatan Masyarakat, 2015)
ABSTRACT Domestic Violence is a serious social problem which the response from the community, because the scope is closed and occurs in the area of the family. The case still in P2TP2A signed in 2009 by as much as 6 cases reported, and as many as 15 cases in 2010, 2011, 2012, as many as 30 cases of as many as 24 cases, 2013 as much as 18. The purpose of this research is to know the physical and psychological Impact of the wife who became a victim of domestic violence in the P2TP2A province of East Kalimantan using approaches phenomenology. This research shows the impact of Psychology experienced by victims of violence is, depressed, confused, sad, stes, despair, frustration, trauma, and changes in behavior such as emotional. Conclusion of this research is the impact of the violence experienced by victims of serious impacts on the conditions of the psychic and the behavior of the victim.It is recommended to the victim so that victims of domestic violence are more open and sharing about the problems that plagued his closest people to people.